1988
DOI: 10.1007/bf02990143
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-selenium interaction in the rat

Abstract: Retention, dynamics of 75Se and 65Zn distribution, and elimination were studied in rats after separate or joint single doses of these metals. White female Wistar rats were divided into four groups (fifteen rats each). Group I received Na2(75)SeO3 (0.1 mg Se/kg i.g.), group II received Na2(75)SeO3 + ZnCl2 (5 mg Zn/kg s.c.), group III received 65ZnCl2, and group IV received 65ZnCl2 + Na2SeO3. The zinc and selenium contents in the tissues were estimated during 120 h after administration; excretion in urine and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…Element contents in whole blood of rats according to the increasing defatted rapeseeds (DRS) rate (mg/kg of dry matter) in the diet (2014) concluded that dietary Se had no effect on Zn levels in rats and chicken. Chmielnicka et al (1988) observed increasing Zn content in rats exposed to single-dose applied inorganic Se. These findings indicate that the potential effect of Se on the other essential elements depends on many factors such as animal species, Se dose, Se species applied, single vs long-term Se application etc.…”
Section: Resultsmentioning
confidence: 82%
“…Element contents in whole blood of rats according to the increasing defatted rapeseeds (DRS) rate (mg/kg of dry matter) in the diet (2014) concluded that dietary Se had no effect on Zn levels in rats and chicken. Chmielnicka et al (1988) observed increasing Zn content in rats exposed to single-dose applied inorganic Se. These findings indicate that the potential effect of Se on the other essential elements depends on many factors such as animal species, Se dose, Se species applied, single vs long-term Se application etc.…”
Section: Resultsmentioning
confidence: 82%
“…Zn-Se was highly significantly correlated in urine and feces. The effects of the Zn-Se interaction were described in a previous animal experiment in which administration of Zn induced a decrease in urinary Se excretion, whereas a visible decrease in fecal Zn excretion was observed in the presence of Se [11]. The mechanisms of these interactions are not known.…”
Section: Zincmentioning
confidence: 84%
“…In particular, it has been shown that zinc supplementation in dialysis patients increases serum selenium concentration (Guo et al, 2013). A simultaneous administration of selenium and zinc resulted in enhanced trace elements retention in organs and tissues (Chmielnicka et al, 1988). Moreover, selenium supplementation has also been shown to increase tissue selenium in animals fed both zinc-adequate and zinc-defi cient diet (Fatmi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, zinc administration decreased selenium retention only at higher zinc:selenium ratio (10:1) whereas no antagonism was observed at a 2:1 ratio (Eybl et al, 1986). At the same time, Chmielnicka and the coauthors have demonstrated lower urinary selenium excretion after zinc treatment (Chmielnicka et al, 1988).…”
mentioning
confidence: 98%